2021
DOI: 10.3390/biology10050408
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Interactions between Primary Hepatocytes and Non-Parenchymal Cells on Physiological and Pathological Liver Stiffness

Abstract: Chronic liver disease is characterized by progressive hepatic fibrosis leading to the formation of cirrhosis irrespective of the etiology with no effective treatment currently available. Liver stiffness (LS) is currently the best clinical predictor of this fibrosis progression irrespective of the etiology. LS and hepatocytes-nonparenchymal cells (NPC) interactions are two variables known to be important in regulating hepatic function during liver fibrosis, but little is known about the interplay of these cues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…An innovative platform called bio-engineered adhesive siloxane substrate with tunable stiffness based on a polydimethyl siloxane substrate in combination with polyelectrolyte multilayer film-coating technology was developed to engineer mechanically tunable substrates mimicking physiologic and pathologic liver stiffness. 44 , 45 , 46 , 47 , 48 More recently, 3-dimensional (3D) bioprinting has emerged for precise spatial positioning of both cells and biomaterials or bioinks such as alginate together in 3D complex geometries and providing mechanical support. 49 , 50 Nguyen et al 51 have bioprinted hepatocytes and nonparenchymal cells in 3D architecture and developed models of drug-induced liver injury.…”
Section: Liver Scaffolds Matrices and Other Substratesmentioning
confidence: 99%
“…An innovative platform called bio-engineered adhesive siloxane substrate with tunable stiffness based on a polydimethyl siloxane substrate in combination with polyelectrolyte multilayer film-coating technology was developed to engineer mechanically tunable substrates mimicking physiologic and pathologic liver stiffness. 44 , 45 , 46 , 47 , 48 More recently, 3-dimensional (3D) bioprinting has emerged for precise spatial positioning of both cells and biomaterials or bioinks such as alginate together in 3D complex geometries and providing mechanical support. 49 , 50 Nguyen et al 51 have bioprinted hepatocytes and nonparenchymal cells in 3D architecture and developed models of drug-induced liver injury.…”
Section: Liver Scaffolds Matrices and Other Substratesmentioning
confidence: 99%
“…84 The hydrogel stiffness is also very important. 9,85 On the one hand, the scaffolds need to provide structural stability to maintain its shape, but on the other hand, they need to be soft enough for their application in liver tissue engineering (being a soft tissue). From previous research, it is known that hepatocytes are highly influenced by the stiffness of the matrix they are cultured on.…”
Section: Reviewmentioning
confidence: 99%
“…168 Recent studies have shown that, not only inflammation and activation of HSC to produce extracellular matrix affect the progression of ALD to endstage liver diseases, but also pre-existing increases in liver stiffness promote pathological changes in liver cells. Studies conducted on hepatocytes plated on surfaces that mimic the stiffness of healthy (soft gels, 2 kDa) and cirrhotic (stiff gels, 55 kDa) livers revealed that cells grown on stiff surfaces exhibit lower albumin synthesis and cytochrome P450 enzyme activity 169 indicating that extracellular stiffness regulates hepatocyte function. Additionally, hepatocytes plated on stiff matrices and then exposed to second hits, including HCV-HIV coinfections, exhibited higher levels of apoptosis and viral infectivity.…”
Section: Ald Modifiersmentioning
confidence: 99%